Advancing a MEMS-Based 3D Cell Culture System for in vitro Neuro-Electrophysiological Recordings - Bastiaens, Alex J.; Frimat, Jean-Philippe; van Nunen, Teun; Schurink, Bart; Homburg, Erik F. G. A.; Luttge, Regina (Frontiers in Mechanical Engineering, 2018)
In this work we present advances in three dimensional (3D) neuronal cell culture systems based on a reversible assembly of a microbioreactor with a microelectrode array (MEA) to create a MEMS-based 3D cell culture system for in vitro neuro-electrophysiological recordings. A batch of six molds were milled in poly (methyl methacrylate). The molds were used for soft lithography of polydimethylsiloxane (PDMS). In the center of the PDMS shape, a porous polyethersulfone (PES) cylindrical tube was press-fitted to form a growth barrier between the culture chamber inside the PES tube and the microfluidic channel surrounding the PES tube. A thin layer of partially cured PDMS was used to seal the bottom of the microbioreactor and provide reversible adhesion with the glass surface of a MEA. SH-SY5Y cells were successfully differentiated inside the microbioreactors in Matrigel and demonstrated extended neuronal networks over a height of at least 184 micrometers within the system. In previous microbioreactor designsvisibility was limited due to the closed top with the dispensing holes. The new open top design allows for a better evaluation of the cell culture by optical detection methods during the experiment. . Electrophysiological activity was recorded within the microbioreactor using human induced pluripotent stem cell-derived cortical neurons cultured in Matrigel, in 3D, up until 21 days in vitro In summary, we present advances made in the design, the fabrication process and integration of microbioreactors with MEAs. Optical imaging capabilities improved significantly with an open top and the culture time was further extended from 7 to 21 DIV without leakage or degradation thanks to introducing PES as a barrier material and an enhanced assembly procedure. The latter facilitated a sufficient long-term culture for neurons to mature in an environment free from flow-induced stress and provided a proof of principle for. the recording of electrophysiological activity of cortical neurons cultured in 3D.